Тройные диаграммы состояния Cu-Pd (Me=Ag, Au, Ni, Pt). Анализ и построение - Клопотов В. Д. Владимир Дмитриевич; Морозов М. М. Максим Михайлович; Маркова Т. Н. Татьяна Николаевна; Потекаев А. И. Александр Иванович; Клопотов А. И. Анатолий Анатольевич; Кулагина В. В. Валентина Васильевна (2013, 2013)
В фонде НТБ ТПУ отсутствует